The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.3354/dao001049
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cadmium to free-living marine and brackish water nematodes (Monhystera microphthalma, Monhystera dis-juncta, Pellioditis marina)

Abstract: Cadmium toxicity to 3 marine and brackish-water nematodes (Monhystera microphthalma, M. disjuncta, Pellioditis marina) was estimated under static tests. These nematodes are very resistant to cadmium poisoning. LC 50 values are extremely time-dependent; an exposure time of 96 h underestimates the degree of toxicity. For M. rnicrophthalrna LC 50 values decreased from 23.6 ppm after 96 h to 5.4 ppm after 312 h. For M. disjuncta LC 50 values were 21.2 and 18.4 ppm after 192 and 264 h respectively. P. marina was mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…It has been suggested that marine nematodes do not accumulate lipids for energy storage [27] indicating that nematode fatty acid composition reflects membrane fatty acid composition, however, information remains scant. In this study we will focus on the marine free-living nematode Halomonhystera disjuncta (formerly known as Geomonhystera disjuncta), which is known for its high resistance to environmental stress, especially to heavy metals and temperature changes [25,[75][76][77]. H. disjuncta and sister species has been reported both in shallow-water [15,47,74] and in deep-sea environments [53,71].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that marine nematodes do not accumulate lipids for energy storage [27] indicating that nematode fatty acid composition reflects membrane fatty acid composition, however, information remains scant. In this study we will focus on the marine free-living nematode Halomonhystera disjuncta (formerly known as Geomonhystera disjuncta), which is known for its high resistance to environmental stress, especially to heavy metals and temperature changes [25,[75][76][77]. H. disjuncta and sister species has been reported both in shallow-water [15,47,74] and in deep-sea environments [53,71].…”
Section: Introductionmentioning
confidence: 99%
“…Nonselective deposit-feeders and omnivores are extremely nonsensitive, they can rapidly increase their density by completely changing the trophic structure of the nematocene. Such structural alteration has been reported for heavily polluted areas of the North Sea where bottom sediments are inhabited by impoverished communities of nematodes composed almost entirely of nonselective deposit-feeding and omnivorous species [30], in ports of the Sea of Japan [16,17], and in microcosm experiments [14,24].…”
Section: Resultsmentioning
confidence: 97%
“…Cuticular adsorption and the absorption of heavy metals cause increased metal contents in the hypoderm [19]. The external part of the three-layer cuticle consists of collagenlike material secreted by nematodes, which contains disulfide bonds that support its tertiary structure and sulfhydric groups ensuring heavy metal binding and detoxification [10,19,21,30].…”
Section: Resultsmentioning
confidence: 99%
“…The type species H. disjuncta (Bastian 1865) is one of the most well-known marine nematodes. As a model species, H. disjuncta (then under generic names Monhystera and Geomonhystera) has been subject of previous studies on morphology and ultrastructure (Geraert et al 1981; Van de Velde and Coomans 1987, 1991, 1992, demography, physiology and energetics (Chitwood and Murphy 1964;Vranken et al 1988;Herman and Vranken 1988;Herman et al 1984), impact of temperature and salinity on life cycle (Gerlach and Schrage 1971;Vranken and Heip 1986), and toxicology (Vranken et al , 1985(Vranken et al , 1989. Data on geographical records of H. disjuncta and related species have been summarized by Gerlach and Riemann (1973), Jacobs (1987) and in some subsequent publications thereafter.…”
Section: Introductionmentioning
confidence: 99%